N-terminal proB-type natriuretic peptide and homocysteine concentrations in athletes - Fagnani, F.; Spaccamiglio, A.; Grasso, L.; Termine, A.; Angeli, A.; Pigozzi, F.; Borrione, P. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: Several studies suggest that intense exercise may increase the athlete`s thrombotic tendency. Available data on those metabolic alteration are still conflicting and their clinical significance is still worth of interest. The aim of the present study was to investigate if widely used markers of cardiac damage such as NT-proBNP levels are affected by homocysteine concentrations during sustained sport activities. METHODS: Seventy-eight competitive, non-professional athletes were enrolled in the study; 70 healthy age matched subjects, recruited from blood donors, served as controls. Besides the general clinical determinations, the assessed variables included homocysteine, folate, vitamin B12, total and HDL cholesterol, LDH, CPK, NT-proBNP and IL-6. RESULTS: The percentages of athletes with normal and elevated homocysteine levels resulted 46% and 54%, respectively. Mean NT-proBNP levels were significantly higher in athletes than in controls (1 176.66±442.15 pg/mL versus 450.34±180.39 pg/mL). No correlation was found between homocysteine and NT-proBNP values. CONCLUSIONS: The previously described "sport related" homocysteine is not related to other markers of cardiovascular stress such as NT-proBNP. Available data suggest that both hyperhomocysteinemia and high NT-proBNP levels in healthy young athletes could be interpreted as markers of metabolic and morphologic adaptation to training rather than a risk factor for cardio-vascular diseases.